2008
DOI: 10.1002/jcb.21695
|View full text |Cite
|
Sign up to set email alerts
|

NF‐κB and epithelial to mesenchymal transition of cancer

Abstract: During progression of an in situ to an invasive cancer, epithelial cells lose expression of proteins that promote cell-cell contact, and acquire mesenchymal markers, which promote cell migration and invasion. These events bear extensive similarities to the process of epithelial to mesenchymal transition (EMT), which has been recognized for several decades as critical feature of embryogenesis. The NF-kB family of transcription factors plays pivotal roles in both promoting and maintaining an invasive phenotype. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
316
2
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(334 citation statements)
references
References 116 publications
12
316
2
4
Order By: Relevance
“…[14][15][16] NFκB induces EMT via regulation of the expression of multiple matrix proteases, adhesion molecules and both angiogenic and invasive factors. 14,[17][18][19][20][21] In contrast, inhibition of NFκB by various means suppresses EMT and inhibits tumor cell metastasis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] NFκB induces EMT via regulation of the expression of multiple matrix proteases, adhesion molecules and both angiogenic and invasive factors. 14,[17][18][19][20][21] In contrast, inhibition of NFκB by various means suppresses EMT and inhibits tumor cell metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16] NFκB induces EMT via regulation of the expression of multiple matrix proteases, adhesion molecules and both angiogenic and invasive factors. 14,[17][18][19][20][21] In contrast, inhibition of NFκB by various means suppresses EMT and inhibits tumor cell metastasis. [18][19][20][21][22] Recently, NFκB was identified as a transcriptional activator of an additional EMT-inducer gene product, namely, Snail.…”
Section: Resultsmentioning
confidence: 99%
“…Pathway-Several studies have indicated that transcription factor NF-B activity is involved in both promoting and maintaining an invasive phenotype (40). Western blot analysis showed a 3.4-fold (Ϯ0.18; p Ͻ 0.0008) and a 3.1-fold increase (Ϯ0.07; p Ͻ 0.0011) of IB␣ phosphorylation in K8/18-depleted KLE and HepG2 cells, respectively (Fig.…”
Section: Keratin 8 and 18 Knockdown Increases Nf-b Transcriptional Acmentioning
confidence: 91%
“…Several signaling pathways regulating Snail transcription have been identified (3). Both mitogen-activated protein kinase (MAPK) and NFkB stimulate transcription through regions in the minimal promoter of Snail (9,10) and many signaling molecules implicated in EMT progression use both signaling pathways to mediate their response (10)(11)(12)(13)(14). Other signaling pathways implicated in EMT, including Wnt and phosphoinositide 3-kinase (15,16), use GSK-3 to mediate their responses.…”
Section: Introductionmentioning
confidence: 99%